Traumatic experiences, ICD‐11 PTSD, ICD‐11 complex PTSD, and the overlap with ICD‐10 diagnoses. (29th February 2020) - Møller, L.; Augsburger, M.; Elklit, A.; Søgaard, U.; Simonsen, E.
Abstract : Objectives: This study investigated the frequency of traumatic experiences, prevalence rates of ICD‐11 post‐traumatic stress disorder (PTSD) and complex PTSD (CPTSD), and overlap with ICD‐10 classified disorders in outpatient psychiatry. Method: Overall, 165 Danish psychiatric outpatients answered the International Trauma Questionnaire, the Life Event Checklist, and the World Health Organization Well‐being Index. ICD‐10 diagnoses were extracted from the hospital record. Chi‐square analysis, t ‐tests, and conditional probability analysis were used for statistical analysis. Results: Nearly, all patients (94%) had experienced at least one traumatic event. CPTSD (36%) was more common than PTSD (8%) and had considerable overlap with ICD‐10 affective, anxiety, PTSD, personality, adjustment and stress‐reaction disorders, and behavioural and emotional disorders with onset usually occurring in childhood and adolescence. ICD‐11 PTSD overlapped with ICD‐10 anxiety, PTSD, adjustment and stress‐reaction disorders, and behavioural and emotional disorders with onset usually occurring in childhood and adolescence. A subgroup of patients with ICD‐10 PTSD (23%) did not meet criteria for ICD‐11 PTSD or CPTSD. Conclusion: Traumatic experiences are common. ICD‐11 CPTSD is a highly prevalent disorder in psychiatric outpatients. One quarter with ICD‐10 PTSD did not meet criteria for either ICD‐11 PTSD or CPTSD. PTSD and CPTSD had considerable overlap with ICD‐10 disorders.